Drivers of Soft and Stony Coral Community Distribution on the High-Latitude Coral Reefs of South Africa - Schleyer, Michael H; Porter, Sean N (Advances in marine biology, 2018)
The role of abiotic parameters in determining the distribution of coral communities was assessed on the relatively pristine Maputaland reefs of South Africa from comprehensive reef survey data. The reefs, on which 42 communities could be defined, occur within three geographically separate complexes. Patterns in benthic distribution could be partially explained by latitude and depth, in particular, with slope, turbulence and reef aspect playing far less role in that order. A few species were associated exclusively or in high abundance with some of the communities; in most, it was the ratio of otherwise cosmopolitan species within all of the reef complexes that distinguished them. Complex biotic variables were also considered but not quantified and it is likely that low genetic connectivity and high levels of self-seeding result in a measure of isolation of the communities within a latitudinal gradient.